НЕКОТОРЫЕ ЧЕРТЫ БИОЛОГИИ ЛАУРЕНЦИЙ В ЧЕРНОМ МОРЕ - (:unkn) unknown (Киев : Наукова думка, 1988)
Впервые для лауренций Черного моря описаны генеративная структура популяций четырех массовых видов лауренций и ее изменение в течение года. Приведены результаты исследования анатомо-морфологического строения особей различных генераций.
Certain characters of Laurencia biology in the Black Sea
A generative structure is described for populations of four mass species of the Black Sea Laurencia in different seasons with detection of periods and ways of their propagation. It is shown that differences in the structure of gametophytes and sporophytes are insignificant and concern the shape and sizes of main stem, side branches and cells on the cross-section.